Pengaruh Model Discovery Learning Terhadap Kemampuan Pemecahan Masalah Matematis Siswa kelas X IPA SMA Negeri 8 Padang Tahun Pelajaran 2018/2019 - SHERIN KHAIRUNNISA (Departemen Matematika, 2019)
Problemmsolving of mathematical ability is oneoof learningoobjectoof mathematics thatmshould be achieved byystudents. But in fact mathematical problem solvinggabilities are still not optimal. OneOof the factors that make it happen isslearning that has not been able to facilitate students to developpmathematical problem solvinggability properly. The effortssthatccan be doneone of that is by implementinggthe DiscoverylLearning model. The purposeoof this study is to describewwheterrthe mathematicalpproblem solvinggabilities of students who’s learning usinggthe Discovery Learning model are betterrthan the students abilitiesswho’s using directllearning models and describe students’ mathematicalpproblem solving abilitiessduring the Discovery Learning modellimplementation. This research isccombinationoof quasy experiment andddescriptiveeresearch which design issRandomized Control-GrouppOnly Design. Based onntherresult of dataaanalysis, theemathematical problemmsolving abilitiesoof students whileeusinggthe dDiscovery Learninggmodellhave increased. It can beeconcluded that mathematicallproblemm solving abilities of student’sswho’s learning with theeDiscovery Learning modelaare betterrthan theaabilities of students who’s learninggwithddirect learning modelssin class X IPA SMA Negeri 8 Padang. Keywords – MathematicalpProblem Solving, Discovery Learning Model, Direct Learning